Alignment Between Student Learning Needs and Classroom Learning Models: Case Study - Amalia, Irda; Pratiwi, Dwiyani; Razieb, Luthfy Al; Maab, Siti Husna (Linguists : Journal of Linguistics and Language Teaching, 2024)
This research aims to identify the learning needs of students at SMP Muhamadiyah 3 Depok and the main concern of researcher is analyze the alignment between student learning needs and the learning model applied by teachers. Knowing students' learning needs and using appropriate learning models in the classroom is very important in supporting students to achieve learning objectives. The method used in this research is case study. The data were collected by interview and observation. The structure interview distributed to six students from two different VIII classes in the 2023/2024 academic year students and two teachers. Data analysis techniques in this study used narrative analysis. The findings of this research shows that that students' English language skills are still at A1 or Pre-A1 level and face problems such as regular and irregular verbs, spelling, pronunciation, lack of vocabulary, self-confidence speaking in English, limited learning resources, and lack of motivation in learning English. Furthermore, regarding to their learning needs, they wanted more practical learning in English such as speaking English, prefer teaching materials related to fiction and storytelling, and prefer to learn using a combination of learning media such as pictures and videos rather than just using books and worksheets. While, the implementation of the learning model, in this case, did not align with the students' needs, and the teacher still used the lecture method and teacher centers which made students less motivated and contributed during the learning process. Therefore, based on the research findings, it is recommended that teachers have a good understanding of what students need in their learning so the teacher can implement the appropriate model learning that facilitates their learning and able to achieve the learning objectives.